(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
New bisphenol monomers, (4-fluoro)phenylhydroquinone and (3,4-bifluoro) phenylhydroquinone, were prepared in a two-step synthesis. Poly(aryl ether ketone)s were derived from these bisphenols via a nucleophilic aromatic substitution polycondensation with 4,4'-Difluorobenzophenone. The polycondensation proceeded quantitatively in N,N-dimethyl acetamide (DMAc) in the presence of anhydrous potassium carbonate and afforded the polymers with inherent viscosities of 0.50 and 0.92 dL/g. The glass transition temperatures were 151°C and 159°C respectively. The polymers also had high thermal decomposition temperatures and the temperatures of 5% weight loss were all above 527°C and the 10% weight loss were above 587°C in nitrogen atmosphere. There were no melting endotherms that were observed on DSC traces, which indicated that the copolymers were amorphous and the amorphous structures were further confirmed by wide-angle X-ray diffraction. The polymers' solubility was improved by the introduction of bulky pendant groups and all of them exhibited good solubility in some common solvents such as NMP, DMF, DMSO, CH2Cl2, THF, CHCl3 etc. Transparent, strong and flexible films were formed by the DMAc solutions of the polymers with tensile strengths of 98.3 MPa, 95.2 MPa, Young's moduli of 2.74 GPa, 3.06GPa and elongation at break of 27%and 32%. The dielectric constants at 1 MHz of the polymers were 2.82 and 2.75.